Blasting Design and High-Energy Explosive Strategies to Achieve Fines Targets for Mill Performance - Diego Sanchez; Jorge Cardenas (International Society of Explosives Engineers, 2026)
Maximizing SAG mill throughput and metallurgical recovery in hard rock operations requires achieving target fragmentation, particularly a sufficient proportion of fines (<25.4 mm). These fines thresholds are strongly influenced by rock mass competency, commonly characterized using the Axb parameter (30–70) from the JK Drop Weight Test. In many operations, conventional blasting designs and standard emulsions fail to generate the fines content required for efficient downstream comminution. This study evaluates several advanced blasting strategies aimed at enhancing fines generation in very competent rock masses while maintaining cost-effective drill and blast performance. The first approach focuses on steadily increasing the powder factor (kg/t) as a core strategy, complemented by adjustments in blasthole diameter, reduced burden and spacing, the use of dual initiation points, short inter-hole delays (<25 ms), and optimized sequencing—all aimed at enhancing energy distribution and maximizing fines generation in highly competent rock masses. The second strategy consists of increasing the energy factor (kJ/t) by selecting explosives with higher energetic content and detonation performance. This includes the use of heavy ANFO blends and ultra high-energy emulsions with aluminum-based formulations, achieving Relative Bulk Strength (RBS) values between 180–190 and up to 210–230, respectively. These products offer higher detonation velocity (VOD) and peak pressure, enhancing shock energy transmission and breakage efficiency. Field results in granodioritic porphyries with high uniaxial compressive strength showed a 3–5% increase in fines generation compared to standard emulsions—contributing directly to meeting mill performance targets in high Axb conditions. Combined, these strategies provide a practical and technically validated pathway to achieving fines generation targets required for optimal mill performance. When matched to site-specific rock mass characteristics and integrated with blast monitoring tools, they enable improved fragmentation control, reduced P80, and enhanced plant throughput—without compromising operational efficiency or increasing costs disproportionately